Evaluating the Uncanny Valley Theory Based on Human Attitudes - Unggah, Louis Laja; Abdul Manaf, Ahmad Azaini (Archives of Design Research, 2015)
The uncanny valley theory is an idea that was proposed by Masahiro Mori in 1970 regarding the psychological effects of lifelike robotics (Mori, 1970). The uncanny valley is a phenomenon that occurs in animation and robotics, wherein things that look extremely similar to the human face, but differ slightly from its natural appearance or from its natural movements and expressions, are perceived to be disturbing, uncanny, and revolting (Mewes & Heloir). This study aims to analyze participants’ attitudes towards digital characters in order to understand how the uncanny valley affects audiences. Mori’s graph has been criticized on the grounds that familiarity is difficult to define – that it is difficult to determine which emotion accurately represents the opposite of familiarity, and that the word “familiarity” itself may not actually be an accurate description of a positive human response to human-like entities (Ho, MacDorman, & Pramono, 2008). The word “likability” has been proposed as an alternative translation of Mori’s original word, because it is claimed by some to be a more accurate representation of